Fish intake and risk of mortality due to aortic dissection and aneurysm: A pooled analysis of the Japan cohort consortium. Issue 4 (August 2019) - Yamagishi, Kazumasa; Iso, Hiroyasu; Shimazu, Taichi; Tamakoshi, Akiko; Sawada, Norie; Matsuo, Keitaro; Ito, Hidemi; Wakai, Kenji; Nakayama, Tomio; Kitamura, Yuri; Sado, Junya; Tsuji, Ichiro; et al.
Summary: Background & aims: Many studies have suggested that fish intake is associated with protection from risk of atherosclerotic diseases; however, this association with aortic diseases has not been elucidated worldwide. We hypothesized that fish intake is inversely associated with mortality from aortic diseases (aortic dissection and aneurysm). Methods: The study was conducted as a pooled analysis of original data from a maximum of 8 cohort studies, comprising a total of 366, 048 community-based men and women who had no history of cardiovascular disease or cancer. In each cohort, we used Cox proportional hazards regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality from aortic dissection, aneurysm and total aortic disease according to the frequency of fish intake and estimated summary HRs derived from each study. Results: Nonlinear inverse associations were found between fish intake and total aortic disease. Compared with persons who ate fish 1–2 times/week, persons who seldom ate fish had higher mortality from total aortic disease (multivariable-adjusted pooled HR = 1.93; 95% CI, 1.13–3.31). Higher mortality was not seen in those who ate fish 1–2 times/month. A similar pattern was observed for aortic dissection. Regarding aortic aneurysm, both persons who seldom ate fish and those who ate fish 1–2 times/month had higher mortality (HR = 1.99; 95% CI, 0.90–4.40 and HR = 1.86; 95% CI, 0.87–3.98, respectively). Conclusions: Persons who seldom ate fish had higher mortality from aortic dissection, aneurysm, and total aortic diseases. Highlights: Fish intake may have a protective role for developing aortic diseases, but no epidemiological studies exist on this issue. In this pooled analysis, we first identified that low fish intake was a risk factors for mortality from aortic diseases. A threshold was suggested between the seldom and 1–2 times/month categories of fish intake.